3D bioprinted complex constructs reinforced by hybrid multilayers of electrospun nanofiber sheets. (28th March 2019) - Yoon, Yeji; Kim, Chae Hwa; Lee, Ji Eun; Yoon, Jonghun; Lee, Nak Kyu; Kim, Tae Hee; Park, Suk-Hee
Abstract: Despite the usefulness of hydrogels for cell-based bioprinting, the fragility of their resulting constructs has hindered their practical applications in tissue engineering research. Here, we suggest a hybrid integration method based on cell-hydrogel bioprinting that includes alternate layering of flexible nanofiber (NF) sheets. Because the bioprinting was implemented on a nanofibrous surface, the hydrogel-based materials could be printed with enhanced shape resolution compared to printing on a bare hydrogel. Furthermore, the insertion of NF sheets was effective for alleviating the shrinkage distortion of the hydrogel construct, which is inherently generated during the crosslinking process, thereby enhancing shape fidelity throughout the three-dimensional (3D) architecture. In addition to the structural precision, the NF-embedded constructs improved the mechanical properties in terms of compressive strength, modulus, and resilience limit (up to four-fold enhancement). With structural and mechanical supports, we could 3D fabricate complex constructs, including fully opened internal channels, which provided a favorable perfusion condition for cell growth. We confirmed the enhanced bioactivity of the NF-embedded bioprinted construct via cell culture experiments with 80% enhanced proliferation compared to the monolithic one. The synergistic combination of the two flexible materials, NFs and hydrogels, is expected to have extensive applicability in soft tissue engineering.